2005
DOI: 10.1523/jneurosci.4384-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Shal and Shaker Differential Contribution to the K+Currents in theDrosophilaMushroom Body Neurons

Abstract: Shaker, a voltage-dependent Kϩ channel, is enriched in the mushroom bodies (MBs), the locus of olfactory learning in Drosophila. Mutations in the shaker locus are known to alter excitability, neurotransmitter release, synaptic plasticity, and olfactory learning. However, a direct link of Shaker channels to MB intrinsic neuron (MBN) physiology has not been documented. We found that transcripts for shab, shaw, shaker, and shal, among which only Shaker and Shal have been reported to code for A-type currents, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 70 publications
5
41
1
Order By: Relevance
“…6) and suggest the possibility that I A is upregulated in adult cac neurons as well. It is worth noting that Shal mRNA level was not altered in cac neurons, although Shal, rather than Sh, channels are considered to be the dominant contributor to I A in the neuronal soma Baro et al, 1997;Gasque et al, 2005;Peng and Wu, 2007). These data suggest an interesting possibility that Sh plays a role in neuronal plasticity for upregulation and downregulation of neuronal excitability during environmental challenges or behavioral conditioning.…”
Section: Discussionmentioning
confidence: 85%
“…6) and suggest the possibility that I A is upregulated in adult cac neurons as well. It is worth noting that Shal mRNA level was not altered in cac neurons, although Shal, rather than Sh, channels are considered to be the dominant contributor to I A in the neuronal soma Baro et al, 1997;Gasque et al, 2005;Peng and Wu, 2007). These data suggest an interesting possibility that Sh plays a role in neuronal plasticity for upregulation and downregulation of neuronal excitability during environmental challenges or behavioral conditioning.…”
Section: Discussionmentioning
confidence: 85%
“…This technique has uncovered transporters involved in morphogenetic events in both vertebrates and invertebrates (Duboc et al, 2005;Etter et al, 1999;Gasque et al, 2005;Hibino et al, 2006;Pyza et al, 2004;Shimeld and Levin, 2006).…”
Section: Amputation Procedures and Pharmacological Regeneration Screenmentioning
confidence: 99%
“…Since Wu et al (1983) first reported that dissociated Drosophila larval neurons could be maintained in culture for more than a week, larval brain dispersions, from which MBNs can be identified by tissue-restricted expression of a reporter protein, have been used for the study of VDICs (Wright and Zhong, 1995;Delgado et al, 1998;Gasque et al, 2005). Olfactory learning is not an adult specific trait.…”
Section: Ion Channels In Mushroom Bodies Neuronsmentioning
confidence: 99%